The design of thermal imaging camera for observing thermal map during electrical installation practical - Mochammad Darwis (Jurnal Teknologi dan Manajemen Pengelolaan Laboratorium, 2020)
Many cases of fire due to electrical short circuit facilities or inadequate electrical maintenance, require technology in the field of preventive maintenance. Educational materials and knowledge regarding the prevention and handling of damage and the dangers resulting from abnormal heat, must be taught in the practice class, in particular the electrical installation practice. The use of photo infrared thermography to analyze the distribution of excess heat (overheating) at the cable connection points and the constituent electrical components is a new necessity. The still expensive thermal camera led to an inexpensive prototype but still had the same result. The infrared camera prototype was made from the M5Stack microcontroller module and the AMG8833 infrared thermal sensor. The camera was used to check the heat patterns that occured in electrical and mechanical equipment during the operation. The temperature data recorded from the AMG8833 sensor were in the form of an array of data measuring 8x8 pixels which then were proceeded using an interpolation technique to get an even bigger size, 64x64 pixels. The temperature data were presented in a form of certain colors which represented the measured temperature. The prototype results were compared with the standard HT-02 thermal camera resulting in 0.001% of error.